(untitled) (Fisioterapia e Pesquisa, 2022)
The aim of this longitudinal study was to analyze monthly phone calls and calendars as record of falls rate in community-dwelling older adults over 22 weeks, and to verify factors related to adherence to the fall calendar. Participants underwent an assessment composed by anamnesis, level of physical activity, neuropsychological measures and mobility. They also received a schedule of falls that should be completed over 22 weeks, on the day(s) that the event occurred. In addition, the volunteers received monthly phone calls to inquire about occurrence of falls over time. For data analysis, a significance level of α= 0.05 was adopted and the SPSS software (20.0) was used to perform statistical tests. The two tools were compared regarding "sensitivity" and "specificity". The final sample was composed by 52 older adults, with a mean age of 70.5 years old. The adherence to the calendar was 63.4% compared to phone calls. Of nine participants who reported falls by phone calls, three notified them in the calendar, resulting in a sensitivity of 33%. Of the 43 people who did not report falls by phone calls, 31 delivered the calendar without registration. Thus, the specificity of the calendar was 72%. Years of schooling, the Mini Mental State Exam score and the Addenbrooke's Cognitive Examination - revised version score significantly influenced adherence to the fall calendar. In conclusion, there was a greater registration of falls by the monthly phone call compared to the calendar tool in community-dwelling older adults.